International experience in implementing autonomy and self-responsibility mechanisms for public R&D organizations - Nguyen Thi Minh Hanh; Nguyen Hong Anh (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2024)
Japan and the US represent a group of countries with advanced science and technology development, which have built and developed a research system with many achievements and outstanding contributions to the country's socio-economic development as well as science and technology. China is one of the countries that applies the Soviet model of organizing a research system. Recently, there have been many major and continuous reforms in the system and moved closer to the model of research organization system of the world’s advanced countries. Based on the experience of implementing autonomy and self-responsibility mechanisms of public R&D organizations in these 3 countries, the authors have proposed some useful lessons for Vietnam in implementing autonomy and self-responsibility mechanisms for public R&D organizations in the coming time. Code: 24041501